2022
DOI: 10.1007/s10499-022-01023-1
|View full text |Cite
|
Sign up to set email alerts
|

Virulence genes contributing to Aeromonas veronii pathogenicity in Nile tilapia (Oreochromis niloticus): approaching the development of live and inactivated vaccines

Abstract: This study aimed to develop and evaluate live and inactivated vaccines to Aeromonas veronii pathogenicity in Nile tilapia. Therefore, five well-identified Aeromonas veronii isolates, including A (HY1), A (HY2), A (HY3), A (HY4), and A (HY6) isolated from diseased Nile tilapia (Oreochromis niloticus), were used for vaccine preparation. Virulence genes detected by a polymerase chain reaction (PCR) and lethal dose determination were conducted. Nile tilapia, each with a body weight of 25 ± 0.5 g were divided into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 44 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…It is assumed that the virulence genes of A. veronii plus its toxic products are responsible for its pathogenicity, which negatively affects the health and performance of fish, resulting in these abnormalities. As reported by Youssef et al ( 2023 ), A. veronii has alt, fla, lipase, aerolysin, and act genes, identifying them as the primary cause of its pathogenicity. Another document verified virulence factors for A. veronii , including outer membrane proteins, proteases, toxins, secretory enzymes, and hemolytic and cytotoxic activities (Chen et al 2019 ).…”
Section: Discussionmentioning
confidence: 73%
“…It is assumed that the virulence genes of A. veronii plus its toxic products are responsible for its pathogenicity, which negatively affects the health and performance of fish, resulting in these abnormalities. As reported by Youssef et al ( 2023 ), A. veronii has alt, fla, lipase, aerolysin, and act genes, identifying them as the primary cause of its pathogenicity. Another document verified virulence factors for A. veronii , including outer membrane proteins, proteases, toxins, secretory enzymes, and hemolytic and cytotoxic activities (Chen et al 2019 ).…”
Section: Discussionmentioning
confidence: 73%
“…sobria from frozen fish. Tyagi et al (2022) and Youssef et al (2022) discovered a lipase gene in A. veronii isolated from L. rohita and tilapia. Lipases are essential for bacterial feeding (Pemberton et al, 1997), although some studies have found that A. hydrophila with mutant lipase gene lowers lethality, which shows that the role of lipase as virulence factor (Merino et al, 1999).…”
Section: Resultsmentioning
confidence: 99%
“…The potency of the vaccine could be dependent on many levels including bacterial strain and virulence factors present. Virulence genes in other A. veronii strains such as aerolysin (aerA), lipase, cytotoxic enterotoxin (alt) among others (Youssef et al, 2023) showed 90-100% mortality in pathogenicity tests. The virulence of the isolate was estimated from the lethal dose concentration determined for the isolate.…”
Section: Discussionmentioning
confidence: 99%
“…The virulence of the isolate was estimated from the lethal dose concentration determined for the isolate. The application of the isolate as an oral vaccine in aquaculture farms is possible as suspected cross protection between Aeromonas species due to common virulence factors shared by the aeromonads (Youssef et al, 2023).…”
Section: Discussionmentioning
confidence: 99%